2021
DOI: 10.3389/fnins.2020.626497
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Psychological Disorders Caused by Chronic Pain: A Review and Future Directions

Abstract: Accumulating evidence supports an association between chronic pain and psychological disorders, a connection that seems to be bidirectional. Treating both the pain and psychological conditions together is essential for effective treatment outcomes. Acupuncture is a somatosensory-guided mind–body therapy that can tackle the multidimensional nature of pain with fewer or no serious adverse effects. In this review, we discuss the use of acupuncture in some conditions with a high incidence of psychological disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 94 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Electroacupuncture (EA) is a treatment method that combines traditional acupuncture with electrical nerve stimulation based on the basic theory of traditional Chinese medicine. Both animal and human studies have shown that EA can significantly improve chronic inflammatory pain and pain-induced disorders ( Lin et al, 2020 ). Our previous studies have demonstrated that EA relieved chronic inflammatory pain and pain-related anxiety by downregulating PKMzeta expression and upregulating the neuropeptide S (NPS)/NPSR system in the anterior cingulate cortex (ACC) ( Du et al, 2017 ; Du et al, 2020 ; Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture (EA) is a treatment method that combines traditional acupuncture with electrical nerve stimulation based on the basic theory of traditional Chinese medicine. Both animal and human studies have shown that EA can significantly improve chronic inflammatory pain and pain-induced disorders ( Lin et al, 2020 ). Our previous studies have demonstrated that EA relieved chronic inflammatory pain and pain-related anxiety by downregulating PKMzeta expression and upregulating the neuropeptide S (NPS)/NPSR system in the anterior cingulate cortex (ACC) ( Du et al, 2017 ; Du et al, 2020 ; Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture can improve pain-related mood disorders (Shi et al, 2020) and alleviate retrieval of pain memory (Sun et al, 2015). In a word, acupuncture can manage the multidimensional nature of pain with the capability of restoring homeostasis, (Li et al, 2017;Lin et al, 2020) which seems to be an optimal adjuvant therapy (Tseng et al, 2014). More importantly, this complies with the holistic concept of traditional Chinese medicine, because Chinese medicine believes that the human body is an organic whole.…”
Section: Discussionmentioning
confidence: 95%
“…In conclusion, sham acupuncture could be defined as a useful “inactive” control, so even if acupuncture treatment was not superior to sham acupuncture in some researches, we could not ignore the effect of acupuncture ( Lin et al, 2020 ). Meanwhile, there was no single adequate sham intervention for acupuncture trials and the choice of sham acupuncture should depend on the aims ( Dincer and Linde, 2003 ), such as answering specific questions on the composite influence of the various manipulated variables (location, depth, manipulation, de qi, etc.).…”
Section: Discussionmentioning
confidence: 99%